Socialization of Waste Management in Klawalu Mangrove Forest Tourist Attraction Area of Sorong City - Disabella Dayera; Roger R. Tabalessy; Ahmad Rizal Nurul Kusumawardana; Ishak Aryanto; Rosa O. Sapulette; Christina Bastian (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Waste can damage the beauty of the environment and is a threat to humans and ecosystems that are directly affected if not appropriately managed. Public understanding of the impact of waste needs to be improved. So, community service is carried out to provide understanding to the community about handling sound waste and its management around the Klawalu mangrove tourism area so that this place becomes a tourist attraction that the community loves. The methods used in this service are lecture and discussion methods. The results of the service activities found that the community only understood the impact caused by waste in depth. However, with this socialization, the community realizes it is necessary to manage the garbage in the area to produce a clean and beautiful area that is free from garbage. Based on the findings of this study, providing the community with training and fostering a sense of environmental stewardship is essential to cultivating a healthy and pristine environment.